2020
DOI: 10.15294/jdm.v11i2.22876
|View full text |Cite
|
Sign up to set email alerts
|

Job Embeddedness: a Strategy to Reduce Voluntary Turnover Intention

Abstract: This study examines the relationship between Job Embeddedness and Job Insecurity to voluntary turnover intention and job performance. The sample of this study were 209 respondents from permanent or contract employees who worked as secretaries, clerical or administrative personnel in government or private offices in Central Java, Indonesia. This study used Structural Equation Modelling (SEM) for hypothesis testing. Result of this job insecurity cannot be used to predict voluntary turnover intention or job perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Employees who have high work embeddedness reduce their desire to resign, because a sense of comfort makes them attached to the company, especially if they already have an affective commitment, turnover intention will be eroded. This was explained in previous studies of the relationship between turnover intention and job embeddedness (Yang et al, 2019) (Ratnawati et al, 2020), as well as an emphasis on turnover intention and job embeddedness (Li et al, 2021) (Ghosh and Gurunathan, 2015). Some research showed a significant contribution to affective commitment on intention to move this is supported by previous research (Kašpárková et al, 2018) (Kholiq and Miftahuddin, 2017), and (Li et al, 2021) contribution of affective commitment on intention move.…”
Section: Job Embeddedness Affective Commitment and Turnover Intentionsupporting
confidence: 60%
See 1 more Smart Citation
“…Employees who have high work embeddedness reduce their desire to resign, because a sense of comfort makes them attached to the company, especially if they already have an affective commitment, turnover intention will be eroded. This was explained in previous studies of the relationship between turnover intention and job embeddedness (Yang et al, 2019) (Ratnawati et al, 2020), as well as an emphasis on turnover intention and job embeddedness (Li et al, 2021) (Ghosh and Gurunathan, 2015). Some research showed a significant contribution to affective commitment on intention to move this is supported by previous research (Kašpárková et al, 2018) (Kholiq and Miftahuddin, 2017), and (Li et al, 2021) contribution of affective commitment on intention move.…”
Section: Job Embeddedness Affective Commitment and Turnover Intentionsupporting
confidence: 60%
“…Turnover intention can be used as a result of several factors or functions they exist directly in the organization for example regulatory policies,incentive strategies, and organizational culture (Idiegbeyan-ose et al, 2018). But according to (Ratnawati et al, 2020) the intention of employees to change organizations will greatly affect the organization, especially if those who will resign are experts, it will risk transferring knowledge about the company to competing companies (Kartika and Purba, 2018). Therefore, it is said that employees who are satisfied with all work, salary, supervision, promotion, and co-workers, voluntarily identify themselves as part of the organization by conforming base on values, ideal, role, and the objectives of the organization.…”
Section: Introductionmentioning
confidence: 99%
“…They found that fit factor is most suited to explaining retention in the United States, while the link factor is better in India. The work from Wissawapaisal and Chaiprasit (2015) found that organizational fit had no effect on voluntary turnover intention, whereas link and sacrifice do in a Thai sample in line with the work of Ratnawati et al (2020), who examined 209 respondents from Indonesia. We can see that many of the findings using Asian samples are not in line with previous work from other Westerners.…”
Section: Introductionmentioning
confidence: 74%
“…Included studies The following studies were included in the current meta-analysis. Supplementary data can be found online at https://tinyurl.com/appendix-metaanalysis-sea Thai Samples: Ampofo et al (2017); Dechawatanapaisal (2017); Dechawatanapaisal (2018a); Dechawatanapaisal (2018b); Popaitoon and Techalertsuwan (2020); Sawathwej and Setthakorn (2019); Setthakorn (2019); Setthakorn (2020); Suruchthanano (2021); Tantiboontaweewat and Maneesri (2013); Wissawapaisal and Chaiprasit (2015) Indonesian Samples: Ananda and Pane (2017); Atan and Purba (2018); Bambacas (2012); Ciptaningtyas et al (2017); Kismono (2011); Maska and Riyanto (2020); Purba et al (2015); Purba et al (2016); Ratnawati et al (2020); Savira (2018); Sudarti et al (2021) …”
mentioning
confidence: 99%
“…In this regard, Cummings (2020) (54) reported that, the servant-leader is the perfect ethic goodness for a nurse as human, or the general quality of goodness, or moral excellence. Additionally, Ratnawati, (2020) (55) stated that, organizational link has some indicators, such as providing employees the opportunity to participate in all work, allowing them to long interact with peers at work, and having close friends in organization. Accordingly, Zeng & Xu (2020) (56) reported that, Followers of servant leaders feel emotionally protected, which increases their readiness to come up with new ideas, feel autonomous, and take on new tasks.…”
Section: Discussionmentioning
confidence: 99%